ANALISIS PENGARUH INFLASI DAN NILAI TUKAR TERHADAP JAKARTA ISLAMIC INDEX PERIODE TAHUN 2020-2022 - Fitria, Tifany Anis; Riskayanto, Riskayanto; Hidayatullah, Maulana Syarif (LPPM - STIE SAKTI ALAM KERINCI, 2024)
This research aims to determine the influence of inflation and exchange rates on the Jakarta Islamic Index. The method used in this research is quantitative, the data analysis technique in this research uses multiple linear regression analysis and the sampling technique uses purposive sampling technique. This research focuses on macroeconomic variables, especially inflation and the USD/IDR exchange rate, on the JII during the period January 2020 to December 2022. The results of this research show that partially, Inflation (X1) has a significant positive influence on the Jakarta Islamic Index, while the Exchange Rate (X2) has a negative influence on the Jakarta Islamic Index. Simultaneously, these two variables also have an influence on the Jakarta Islamic Index which can be seen from its significant value of 0.00 < 0.05.